Теоретичне дослідження взаємодії бульби із спіраллю очисника картопляного вороху - Булгаков, В. М.; Ружило, З. В.; Черновол, М. І.; Свірень, М. О.; Черновол, М. И.; Свирень, Н. А.; Bulhakov, V.; Ruzhylo, Z.; Chernovol, M.; Sviren, M. (ЦНТУ, 2019)
Очищення викопаної з ґрунту картоплі від ґрунтових домішок і рослинних решток є найбільш важливим елементом в її виробництві, оскільки чистота бульб, відсутність пошкоджень і високі експлуатаційні показники самого прибирання в значній мірі визначають ефективність всієї галузі. Створення нових очисників картопляного вороху, менш металомістких, більш ефективних і високопродуктивних дозволяє успішно вирішувати це завдання. Для обґрунтування оптимальних кінематичних і конструктивних параметрів нового очищувача картопляного вороху спірального типу побудована математична модель руху одиничної бульби по очисній поверхні, утвореній двома спіралями. В результаті рішення на ПК отриманих аналітичних виразів були побудовані графічні залежності між параметрами розглянутого процесу руху одиничного тіла бульби картоплі між двома сусідніми спіралями, що дозволили вибирати оптимальні конструктивні і кінематичні параметри спірального сепаратора. Очистка выкопанного из почвы картофеля от почвенных включений и растительных остатков является наиболее важным элементом в ее производстве, поскольку чистота клубней, отсутствие повреждений и высокие эксплуатационные показатели самого процесса уборки в значительной степени определяют эффективность всей отрасли. Создание новых очистителей картофельного вороха, менее металлоемких, более эффективных и высокопроизводительных позволяет успешно решать эту задачу. Для обоснования оптимальных кинематических и конструктивных параметров нового очистителя картофельного вороха спирального типа построена математическая модель движения единичных клубней по очистной поверхности, образованной двумя спиралями. В результате решения на ПК полученных аналитических выражений были построены графические зависимости между параметрами рассматриваемого процесса движения единичного тела клубней картофеля между двумя соседними спиралями, которые позволили выбирать оптимальные конструктивные и кинематические параметры спирального сепаратора. Cleaning of potatoes from soil and plant residues is the most important element in their production, as the purity of the tubers, the absence of damage and the high performance of the harvest itself largely determine the efficiency of the entire industry. The creation of new cleaners of potato residues that are less metal-intensive, efficient and high-performing allows solving this problem successfully. A new design of the spiral-type residue cleaner has been developed. It improves the performance of potato harvesting machines preventing operating elements from sticking with wet soil (by installing spirals with mutual overlapping). The separation intensity is achieved by eccentric installation of spirals. A mathematical model of the movement of a tuber along the cleaning surface formed by two spirals is developed in order to substantiate the optimal kinematics and design parameters of a new spiral-type potato cleaner. On the basis of computer-calculated analytical expressions, graphical dependences between the parameters of the considered process of movement of a tuber between two adjacent spirals were constructed. That allowed identifying the optimal design and kinematics parameters of the spiral separator. While analyzing the kinematics of movement of a tuber along the surface of the spiral-type cleaner under conditions of contact of the tuber at two points to one spiral and at one point to another, we established that as the angular velocity of the spiral rotation increases, the transporting capacity of the operating element also increases, and the separation capacity is somewhat reduced.
Теоретическое исследование взаимодействия клубня со спиралью очистителя картофельного вороха
Theoretical Study of the Interaction of a Tuber with the Spiral of Potato Cleaner
Keywords: картопля; прибирання; очищення від домішок; рух; математична модель; розрахунки на ПК; картофель; уборка; очистка от примесей; движение; математическая модель; расчеты на ПК; potato; harvesting; cleaning from residues; movement; mathematical model; computer calculations